ANALYSIS OF SUPERIOR CROPS LOCATION IN EAST JAVA, INDONESIA - Hanifatus Sahro; Shwu-En Chen; S Sujarwo (Agricultural Socio-Economics Journal, 2021)
Regional development is an important aspect in improving the regional economy, and its relationship with the national economy. East Java Province is one of the regions with the most potential agricultural sector and is the highest national granary area in Indonesia. Maximizing the potential of the resources owned by East Java will accelerate the development process and increase the regional and national economy. For the economic growth,this study aims to examine the crops performance to estimate the pattern of regional economic growth in East Java. The time series data of East Java Central Bureau of Statistics from2008 to 2017 are adopted. The location quotient analysis and shift-share analysis with three indicators, namely regional economic growth, proportional shift growth, and differential shift, are used.The results showed that crops such as corn, green beans, peanuts, soybeans, rice, sweet potatoes, and cassava in 29 districts and 9 cities of East Java have crucial performance and economic growth patterns. As the results, to consider and identify priority policy plans to accelerate regional economic development and growth are suggested.